2020
DOI: 10.3389/fmicb.2020.586412
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Tannic Acid on the Quality of Bacterial Communities Present in High-Moisture Mulberry Leaf and Stylo Silage

Abstract: Tannic acid (TA), a type of polyphenol, is widely distributed in plants, especially in legumes. Not only does it possess antimicrobial properties, but it also has the ability to bind with proteins. The fermentation parameters, nitrogen fractions, antioxidant capacity, and bacterial communities present in mulberry leaves and stylo (Stylosanthes guianensis) ensiled with or without 1 and 2% TA per kilogram of fresh matter (FM) were investigated after 75 days' fermentation. The results showed that 1 and 2% TA both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 53 publications
2
15
1
Order By: Relevance
“…Levels of CT greater than 6% have shown a strong ability to inhibit bacterial activity and protein degradation in silage [ 18 ]. In addition, tannic acid is a type of polyphenol substance analogous to CT (both are a complex group of polyphenolic compounds), and 2% tannic acid can inhibit activity in certain bacteria, including lactic acid and coliform bacteria, and decreased protein degradation during ensiling [ 22 ]. The CT content-level results suggest that there is biological activity of CT in sainfoin materials.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of CT greater than 6% have shown a strong ability to inhibit bacterial activity and protein degradation in silage [ 18 ]. In addition, tannic acid is a type of polyphenol substance analogous to CT (both are a complex group of polyphenolic compounds), and 2% tannic acid can inhibit activity in certain bacteria, including lactic acid and coliform bacteria, and decreased protein degradation during ensiling [ 22 ]. The CT content-level results suggest that there is biological activity of CT in sainfoin materials.…”
Section: Discussionmentioning
confidence: 99%
“…He et al (2019a) also reported that GA had an impact on microbial community. Thus, the variations of microbial communities were strongly associated with different silage qualities (Wang et al, 2020). Surely, WPS ensiled with 0.5 and 1% GA showed a better fermentation quality that might be due to the GA-treated group promoting the microbial communities' composition and abundance and then achieving a better bacterial diversity for desirable silages.…”
Section: Bacterial Diversity Of Whole Plant Soybean Silagementioning
confidence: 98%
“…According to the above analysis, GA addition is helpful to improve fermentation quality of WPS silage. The primary purpose of silage-making is to conserve biomass and reduce nutrient loss of fresh forage (Wang et al, 2020). The CP content of WPS silages was comparable to mulberry leaf silage (Wang et al, 2019) but much higher than stylo silage (He et al, 2019a).…”
Section: Characteristics Of Fresh Whole Plant Soybean Prior To Ensilingmentioning
confidence: 99%
“…Tannic acid at high concentrations has been shown to inhibit bacterial growth on pathogenic microorganisms, such as Staphylococcus aureus [37]. However, in plant-associated bacteria, positive effects of tannic acid were reported [38]. For this reason, first, we tested the possible inhibitory effect of TA-PVA NPs (before and after adding Fe) on the bacterium by determining the minimal inhibitory concentration CMI to fix the maximum applicable concentration of NPs in the subsequent plant experiments.…”
Section: Determination Of Optimal Fenps Dosesmentioning
confidence: 99%